Climate Change Mitigation and Adaptation—ZEMCH 2016 - Arman Hashemi (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This book explores the current issues around sustainable design and energy efficiency within the construction industry in both developed and developing countries. Sustainable housing; thermal comfort; daylighting; low-income housing; green roofs; energy efficient retrofitting and photovoltaic façades are some of the subjects discussed in the book.